The impact of emotional and cognitive biases on the investment decisions of Saudi investors: A multigroup analysis approach - Rahahleh, Naseem Al; Gazzaz, Heba (Asian Economic and Financial Review, 2025)
There is a limited understanding of the impact of emotional and cognitive biases on investment decisions among Saudi investors. This study aimed to investigate the impact of prospect biases on investors’ decisions, considering specific characteristics such as gender differences, education levels, investment experience, investment size, and trading frequency. Online questionnaires were distributed to Saudi investors to explore their perceptions of various prospect biases and their investment decisions. The sample included 598 valid responses for data analysis. A partial least squares-structural equation modeling analysis was conducted using SMART PLS. The results indicate that prospect bias significantly influences investment decisions. However, no significant differences were observed based on gender, investment size, or trading frequency. The findings also show a positively significant impact of prospect bias on investors’ decisions based on their education and experience, aligning with the objectives of the Financial Sector Development Program under Saudi Vision 2030. Prospect biases are prevalent among Saudi investors with limited education and experience. Understanding these biases can improve financial decision-making, leading to better outcomes for individual investors. Policies should focus on enhancing financial education, promoting best trading practices, and establishing mentorship programs to foster rational investment behavior among investors.